A modular and compact portable mini‐endstation for high‐precision, high‐speed fixed target serial crystallography at FEL and synchrotron sources. (8th October 2015) - Sherrell, Darren A.; Foster, Andrew J.; Hudson, Lee; Nutter, Brian; O'Hea, James; Nelson, Silke; Paré‐Labrosse, Olivier; Oghbaey, Saeed; Miller, R. J. Dwayne; Owen, Robin L.
Abstract : The design and implementation of a compact and portable sample alignment system suitable for use at both synchrotron and free‐electron laser (FEL) sources and its performance are described. The system provides the ability to quickly and reliably deliver large numbers of samples using the minimum amount of sample possible, through positioning of fixed target arrays into the X‐ray beam. The combination of high‐precision stages, high‐quality sample viewing, a fast controller and a software layer overcome many of the challenges associated with sample alignment. A straightforward interface that minimizes setup and sample changeover time as well as simplifying communication with the stages during the experiment is also described, together with an intuitive naming convention for defining, tracking and locating sample positions. The setup allows the precise delivery of samples in predefined locations to a specific position in space and time, reliably and simply.